Diagnosis of double aortic arch by cross sectional echocardiography with Doppler colour flow mapping. - Kan, M N (1987)
A case of double aortic arch in a 15 month old boy was diagnosed by cross sectional echocardiography supplemented by Doppler colour flow mapping. These examinations showed two very large vessels communicating with the aorta; the demonstration of anterograde flow in one vessel and retrograde flow in the other enabled a definite diagnosis of Edwards type IA double aortic arch to be made.